Faktor-Faktor Penghambat Penyelesaian Tugas Akhir Skripsi (Studi Kasus Pada Mahasiswa Akuntansi Angkatan 2018 UPN “Veteran” Jawa Timur) - Amaria Purba, Dinda; Munari , Munari (CV RIFAINSTITUT, 2023)
The thesis final project is a scientific work that must be made by final-year students to obtain an academic degree. But in reality, there are still many students who need help in doing the final thesis. This study aims to see and test how psychological well-being, academic ability, thesis administration system, and lecturer guidance influence the completion of the final thesis assignment for accounting students class of 2018 UPN